Let’s face the facts examining Filipinos’ fact-checking Practices in consuming online information in social media - Amante, Joaquim Lorenzo C.; Fernandez, Sophia A.; Talusan, Irish Jane L. (Quezon City University of the Philippines Diliman, 2025)
Reflecting global user behavior, Filipino social media users (SMUs) have started mistrusting social media and engaging in fact-checking. As literature on this is sparse, this study examines how Filipino SMUs practice online fact-checking on social media. It explores their fact-checking environment, engagement in fact-checking, and the influence of demographics, perceived source and message credibility, and social networks. Through an online survey guided by the Information Horizon Theory by Sonnenwald (1999) and insights from relevant literature, the study gathered 861 respondents and found that they are in a social media use context saturated by information in many forms. Here, they encounter fact-checking situations involving political, medical, and educational topics. To resolve these, they often engage in fact-checking through their primary sources of online news and search engines but they do sometimes use their perceived less important sources like fact-checking websites, expert opinions online, and other SMUs. Further, almost all factors were either weak or inconsistent predictors except for social motivation to fact-check, making this the most stable predictor of fact-checking investigated here across all identified types albeit weak. Overall, this provides insights into how to bolster fact-checking through media initiatives, educational and government programs, and truth communities.
Thesis
Keywords: Social media -- Philippines -- Influence; Online social networks -- Philippines